Analysis of IT Service Management at PT Bukit Asam Tbk using the ITIL V4 Framework - Zahara, Alda Putri; Yulhendri (Universitas Mohammad Husni Thamrin, 2026)
PT. Bukit Asam Tbk (PTBA) is a mining company that utilizes information technology to support its business. In practice, IT services play an important role in supporting business operations from production, security, to supply chains. These services are also subject to Incident s and problems such as network disruptions, application troubleshooting, password resets, work device repairs, and access rights requests. Therefore, PTBA needs to implement Incident and Problem Management practices based on the ITIL V4 framework to handle Incident s as quickly as possible, so that their impact can be minimized and repeated Incident s prevented. This study aims to determine the extent of the implementation of Incident and Problem Management practices at PTBA using the ITIL V4 Maturity Level Self Assessment questionnaire. The questionnaire was distributed to eight stakeholders selected through purposive sampling. The results of the study show that the implementation of Incident Management practices at PTBA is at Level 3 (Product) with a gap of 1 from the target level, and Problem Management practices are at Level 3.5 (Quality Control) with a gap of 0.5 from the target level. Core processes such as recording, classification, prioritization, escalation, handling, and closure have mostly been implemented. However, there are weaknesses such as prioritization not being based on impact, and cross-party coordination not being fully structured. Therefore, recommendations were compiled based on ITIL V4 Incident and Problem Management practices, with the hope of helping PTBA improve the quality of its IT services.